Nanosized (Ni1-xZnx)Fe2O4 for water oxidation - Mehrabani, Somayeh; Singh, Jitendra Pal; Bagheri, Robabeh; Wattoo, Abdul Ghafar; Song, Zhenlun; Chae, Keun Hwa; Najafpour, Mohammad Mandi (ROYAL SOC CHEMISTRY, 2019)
Performing water splitting for H-2 production is an interesting method to store different energies. For water splitting, an efficient and stable water-oxidizing catalyst is important. Ni-Fe (hydr)oxides are among the best catalysts for water oxidation in alkaline electrolytes. An Fe amount higher than 50% in Ni-Fe (hydr)oxides increases the overpotential for water oxidation. Thus, Ni-Fe (hydr)oxides with a high ratio of Fe to Ni have rarely been focused on for water oxidation. Herein, we report water oxidation using nanosized (Ni1-xZnx)Fe2O4. The catalyst was characterized via some methods and tested at pH values of 3, 7 and 11 in phosphate buffer. Nanosized (Ni1-xZnx)Fe(2)O(4 )is a good catalyst for water oxidation only under alkaline conditions. In the next step, amperometry studies showed current densities of 3.50 mA cm(-2) and 11.50 mA cm(-2) at 1.25 V in 0.10 M and 1.0 M KOH solution, respectively. The amperometric measurements indicated high catalyst stability in both 0.10 M and 1.0 M KOH. Tafel plots were obtained in KOH solution at concentrations of both 0.10 M and 1.0 M. At pH = 13 in KOH solution (0.10 M), linearity of lg(j) vs. potential was shown, with two slopes relating to both relatively low (170.9 mV per decade) and high overpotentials (484.2 mV per decade). In 1.0 M KOH solution, the Tafel plot showed linearity of lg(j) vs. potential, with two slopes relating to both relatively low (192.5 mV per decade) and high overpotentials (545.7 mV per decade). After water oxidation, no significant change was observed in the catalyst.
Keywords: OXYGEN EVOLUTION REACTION; LAYERED DOUBLE HYDROXIDES; XPS SPECTRA; THIN-FILMS; IRON; NICKEL; CATALYST; METAL; PHOTOANODES; COMPLEX